A Method for Generating Strategy Maps Using Anp - Palominos-Belmar, P; Quezada-Llanca, L (Emerald Group Publishing Ltd., 2014)
Purpose - The purpose of this paper is to present a method for identifying causal relationships in a strategy map.Design/methodology/approach - A strategy map is a visual representation of the strategy of a company, which includes the strategic objectives of a company and the cause-effect relationships between them. Its network structure facilitates its representation as an analytic network process (ANP) model. The proposed method starts with a network with all possible relationships and then it deletes those relationships, which are not important. To do this, it uses the techniques of the ANP approach.Findings - It was found that ANP is a good tool for modelling a strategy map and for identifying the important relationships of a strategy map. A study case of a manufacturing is shown to illustrate how the proposed method can be used in practice.Practical implications - Normally, the cause-effect relationships between strategic objectives are generated in a subjective way. Even this way of working is widely accepted in practice, some studied have shown that the declared relationships are not necessarily valid. The proposed method provides a quantitative tool to establish the relationships between strategic objectives, which are obtained using a method (ANP) that has a strong conceptual base. This is an indication that the strategy map obtained represents in a better way the strategy of the company.Originality/value - ANP is a methodology which is used to estimate the priority of nodes with in a network. In this work ANP is used to estimate the priority of the arcs of the network. The results of application in a company represent a good indication that the method may be implemented in other manufacturing companies. © Emerald Group Publishing Limited.